Chlorophyll-a Concentration in The Lubuk Siam Lake, Lubuk Siam Village, Siak Hulu Sub District, Kampar District - Clarissa, Enny; Siagian, Madju; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractThere are several human activities around the Lubuk Siam Lake such as plantation and agriculture. Anthropogenic activities will influence nutrient in waters.  To understand the concentration of chlorophyll-a in the Lubuk Siam Lake, a research was conducted in February - March 2017. There were 3 stations namely Station 1 (inlet area), Station 2 (fish cage area), and Station 3 (outlet area). In each station, there   were 3 sampling points : at surface  (50cm), 2 secchi depth (126cm) and 3 secchi depth (189 cm). Sampling were taken  once/week for 3 weeks period. Water quality parameters measured were chlorophyll-a, temperature, transparency, pH, dissolved oxygen, free carbon dioxide, nitrate, and phosphate.  Results shown that chlorophyll-a concentration was 12.76 – 44.86 µg/L, temperature 28.5 – 30.5°C, transparency 63 – 89 cm, pH 7.03 – 7.27, dissolved oxygen 4.09 – 7.83 mg/L, free carbon dioxide5.29 – 15.98 mg/L, nitrate 0.069 – 0.168 mg/L and phosphate 0.164 – 0.123 mg/L. Based on the concentration of chlorophyll-a, the Lubuk Siam Lake can be categorized as mesotrophic.Keywords: Chlorophyll-a, mesotrophic, water quality, Lubuk Siam Lake.